Penguatan Komunikasi Bahasa Inggris Siswa Mathayom 1 Melalui Internship di Thailand - Fikri, Muhammad Abdul; Safitri, Washlurachim; Thiprak, Ratchanee (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This community service program aimed to improve the basic English communication skills of Mathayom 1 students at Anuban Chomchon Phukradueng School, Loei Province, Thailand, through an international internship program that provides cross-cultural learning experiences. The program involved 20 students and was conducted over three months with a total of 12 meetings. The methods included needs analysis, lesson planning based on Communicative Language Teaching (CLT), dialogue practice using drilling and repetition techniques, and evaluation through pre-test and post-test in the form of simple conversations, supported by classroom participation observation. The results showed improvements in pronunciation, fluency, accuracy, and confidence, as well as a significant increase in student participation from 30% at the beginning to 85% at the end of the program. Students demonstrated greater confidence in speaking, the ability to sustain simple conversations, and reduced anxiety when performing in front of the class. These findings indicate that a communicative approach combined with repetitive practice in a cross-cultural learning context is effective in supporting the development of speaking skills among beginner-level EFL students. Practically, this program can serve as an alternative teaching strategy for teachers to enhance student participation and confidence by integrating communicative activities with drilling techniques in English language learning.